2023
DOI: 10.1037/sah0000463
|View full text |Cite
|
Sign up to set email alerts
|

Is smoking acceptable for lung cancer patient? Factors influencing the stigmatization.

Camille Auriol,
Nicole Cantisano,
Patrick Raynal

Abstract: Lung cancer is a disease with strong stigma due to stigmatization around smoking. Reducing stigma could be favorable for patients but requires to identify factors influencing this stigmatization. This study aimed to analyze people’s acceptability judgments regarding smokers’ behaviors concomitant to a lung cancer diagnosis. This study used a quantitative method to identify variables involved in one’s judgment, based on a comprehensive combination of scenarios rated by participants on an acceptability scale. Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This result suggested that, even if previous studies showed that health professionals could stigmatize patients [ 21 , 41 , 61 , 81 ], their stigmatization attitudes seemed to be lower than non-health professionals. Supporting this finding, a recent study showed that health professionals had higher acceptability scores regarding a fictious patient with lung cancer who continued smoking, when compared with participants who were not health professionals [ 82 ]. The underlying explanations behind these observations remain to be identified.…”
Section: Discussionmentioning
confidence: 82%
“…This result suggested that, even if previous studies showed that health professionals could stigmatize patients [ 21 , 41 , 61 , 81 ], their stigmatization attitudes seemed to be lower than non-health professionals. Supporting this finding, a recent study showed that health professionals had higher acceptability scores regarding a fictious patient with lung cancer who continued smoking, when compared with participants who were not health professionals [ 82 ]. The underlying explanations behind these observations remain to be identified.…”
Section: Discussionmentioning
confidence: 82%
“…The choice of these four factors was also justified by a recent report focused on acceptability judgments regarding the behaviors of a fictional smoker diagnosed with lung cancer. Indeed, this study showed that participants’ judgments were influenced by four similar factors, including smoking habits, smoking behavior following cancer diagnosis, cancer stage and prognosis, and physical activity [ 58 ]. We thus assumed that an analogy exists between factors related to drinking in colorectal cancer and those related to smoking in lung cancer, which further supported the choice of the four factors listed above.…”
Section: Introductionmentioning
confidence: 99%